2018
DOI: 10.1111/gbi.12305
|View full text |Cite
|
Sign up to set email alerts
|

Hydrocarbon biomarkers preserved in carbonate veins of potentially Paleoproterozoic age, and implications for the early biosphere

Abstract: Research on the early rise of oxygenic photosynthesis and eukaryotes has recently encountered a major pitfall, as some hopane and sterane biomarkers reported in Archaean rocks are the results of contamination. Following an extensive petrological framework in the Pilbara Craton, Western Australia, oil-bearing fluid inclusions and solid bitumens were identified in replacement and hydrothermal carbonate veins cross-cutting Archaean metasedimentary rocks. The 2.55-2.63 billion years old metasedimentary rocks were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 71 publications
(191 reference statements)
0
3
0
Order By: Relevance
“…). Proterozoic carbonates are sources of hydrocarbon biomarkers (Peters and George ); dolomite nodules from an outcrop at Sixtymile Canyon and Nankoweap Butte, Walcott member, Kwagunt Formation, Chuar Group (~751–742 Ma, 1,609 m above base) were one source of important organic biomarkers reported by Brocks et al. ().…”
Section: How Might More Proterozoic Fossils Aid Our Understanding Of mentioning
confidence: 90%
“…). Proterozoic carbonates are sources of hydrocarbon biomarkers (Peters and George ); dolomite nodules from an outcrop at Sixtymile Canyon and Nankoweap Butte, Walcott member, Kwagunt Formation, Chuar Group (~751–742 Ma, 1,609 m above base) were one source of important organic biomarkers reported by Brocks et al. ().…”
Section: How Might More Proterozoic Fossils Aid Our Understanding Of mentioning
confidence: 90%
“…In this figure, the uncertainty about the temperature T is assumed to be only due to the accuracy of the oven thermocouple (±5 • C). (12) and the experimental ones (circle dots) obtained for sample S1 both by gravimetric (Equation (13)) and spectroscopic (Equation (15)) techniques (see Table 1). The error bars relative to the temperature T (in abscissae) and to χ gravimetry (in ordinates) are within the size of the dots.…”
Section: Theory and Experiment: Calcite Decompositionmentioning
confidence: 99%
“…The most interesting mineral phases that are often associated with organic matter are Mg-, Ca-, and Fe-carbonates [8][9][10]. It has been shown that the carbonate matrix can host and protect organic material against relatively high temperatures [11,12]. Similar considerations apply to some sulphates, in particular gypsum, and some phyllosilicates.…”
Section: Introductionmentioning
confidence: 99%